2013
DOI: 10.1007/s00103-013-1791-5
|View full text |Cite
|
Sign up to set email alerts
|

Wissen, Einstellung und Verhalten zur Masernimpfung

Abstract: Achievement of the goal to eliminate measles by 2015 set by the European region of the World Health Organization (WHO) necessitates an increase in the willingness of German nationals to get vaccinated. To identify influential factors on vaccination behavior as the basis for communication measures specific to target groups, the Federal Centre for Health Education (BZgA) has conducted two representative surveys on attitude, knowledge, and practice concerning vaccination among parents of children between 0 and 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
2
0
1
Order By: Relevance
“…Fortunately, only a small proportion of individuals (1.5%) reported negative attitudes towards vaccinations in general, however, 8.9% reported "slightly negative attitudes" (Fig. 2), which is also in agreement with findings form other studies [21]. The association between level of knowledge about vaccination and vaccine acceptance is not straightforward [8].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Fortunately, only a small proportion of individuals (1.5%) reported negative attitudes towards vaccinations in general, however, 8.9% reported "slightly negative attitudes" (Fig. 2), which is also in agreement with findings form other studies [21]. The association between level of knowledge about vaccination and vaccine acceptance is not straightforward [8].…”
Section: Discussionsupporting
confidence: 89%
“…Previous research in Germany has focused on a) specific population subgroups (e.g. children [21], pregnant women [22], elderly individuals [23] or physicians [24]), b) examined various risk factors of poor vaccination uptake not related to KAP (e.g. sociodemographic factors) [2;12] and c) examined only single [21;23] or a few vaccinations [13;25].…”
Section: Discussionmentioning
confidence: 99%
“…This was particularly true for older adults. In Germany, it has been estimated that 3–5 % of the population rejects immunizations in general [36] and one study found that 31 % had some prejudice against particular vaccines [37]. Results from another German study showed that overall, older adults perceived vaccinations as less important than younger people [35].…”
Section: Discussionmentioning
confidence: 99%
“…Nur wer Impfempfehlungen oder Public Health Ziele kennt, kann aktiv an deren Umsetzung mitarbeiten. Ärzte sind die wichtigste Informationsquelle für Patienten hinsichtlich der eigenen Impfentscheidung und der für die Kinder [16]. Daher war es von besonderem Informationswert, das Wissen unserer zukünftigen Ärzte in Bezug auf den eigenen Impfstatus und die Empfehlungen der STIKO zu ermitteln.…”
Section: Diskussionunclassified